Pursuit and Evasion: from singles to groups. Issue 1 (1st March 2022) - Yoshihara, Sota; Ohira, Toru
Abstract: We provide a brief review of the current status of the traditional problem of pursuit and evasion. The new approach proposed by Eliezer and Barton is presented with an example of the one-to-one pursuit and evasion. Consequently, we describe recently proposed "Group Chase and Escape" and its characteristic behaviors. The directions of possible topics for future investigations and possible applications are also discussed.